GRAMMATICAL CATEGORIES OF TRANSITIVE VERBS IN ENGLISH AND UZBEKISTAN - Umarova Munavvar Nurmuhammedovna; Mukumjon Axunov Muhammadaminovich (TADQIQOTLAR, 2025)
ANNOTATION: This article is intended to provide comprehensive information on the theoretical views on the use of the term "concept" in linguistics, to provide a comprehensive overview of the linguistic specific meanings of general concepts , and to present a comprehensive overview of all the means of representation and expression in the field of the study of the term "concept" in linguistics . This is to reveal the phenomena that allow us to draw scientific conclusions and give a broader understanding of the information about the means of the term "concept" .